The significance of environmental issues in Mindanao in the news agenda of Sun Star Davao, Mindanao Times and Mindanao Daily Mirror - Maniquis, John Archival M.
Sun.Star Davao, Mindanao Times and the Mindanao Daily Mirror are three of the local community newspapers in the region. Local newspapers are assumed to have greater scope in news gathering in terms of local events. The study aimed to determine how significant environmental issues are in Mindanao in the news agenda of Sun.Star Davao, Mindanao Daily Mirror and the Mindanao Times. Content analysis by statistical method of analysis is done on the issues of the three newspapers for the whole month of September 2010. each is identified of its article frequency, amount of space given to environmental articles, and the articles' prominence through its placement in the newspapers. The study found out how significant the issue of environmental consciousness was in their news agenda through measuring the size of article (consisting of the title and the photo used using square inches for measurement) and comparing that size on how big the newspaper were that would also determine exactly how big or small that article would be with respect to the size of the newspaper. The study concludes that environmental issues are significant for Mindanao Times, Sun.Star Davao and the Mindanao Daily Mirror. The study guarantees at 95% level of confidence, 2% of their news agenda contained, contains and would still contain environmental news and articles.